Pengaruh Fasilitas Belajar Kompetensi Guru Terhadap Hasil Belajar Mata Pelajaran Matematika Dengan Dimediasi Motivasi Belajar - Chong, Gisella; Alexander, Alexander; Ginting, Sugianta Ovinus; Br. Ginting, Litka Tiadoraria (Jurnal Wira Ekonomi Mikroskil, 2024)
This study aims to determine and analyze the influence of Learning Facilities and Teacher’s Competency toward the Mathematics Learning Outcomes of Class X Students of SMA Wiyata Dharma Medan Mediated by Learning Motivation. This study used a sample of 79 students with probability sampling using saturation sampling. This research uses Structural Equation Modeling (SEM) method with Smart PLS Software program. Testing the direct effect shows that the Learning Facilities variable has a negative and insignificant effect on Learning Outcomes, while the Teacher Competency variable on Learning Outcomes, Learning Facilities on Learning Motivation and the Teacher Competency variable on Learning Motivation have a positive and significant effect. The variables Teacher Competence on Learning Outcomes and Learning Motivation on Learning Outcomes have a positive and insignificant effect. Furthermore, the influence of the Learning Motivation variable in mediating Learning Facilities and Teacher Competence on student learning outcomes is directly positive and not significant. R-Square Adjusted Model = 0.054, meaning that the ability of variables X1 (Learning Facilities) and X2 (Teacher Competence) in explaining Y (Learning Outcomes) is 5.4% thus the model is classified as weak. The R-Square Adjusted Model is valued at 0.336, meaning that the variable ability of X1 (Learning Facilities) and X2 (Teacher Competence) in explaining Z (Learning Motivation) is 33.6%, thus the model is classified as moderate.